2001
DOI: 10.4315/0362-028x-64.9.1341
|View full text |Cite
|
Sign up to set email alerts
|

Hazard Analysis of Escherichia coli O157:H7 Contamination during Beef Slaughtering in Calvados, France

Abstract: To identify hazard points and critical points during beef slaughtering, which is a necessary first step toward developing a hazard analysis and critical control point system to control meat contamination by Escherichia coli O157:H7, samples (n = 192) from surfaces, work tops, worker's hands, and beef carcasses were collected from a slaughterhouse in Calvados, France. Five strains of E. coli O157:H7 were isolated from a footbridge and a worker's apron at the preevisceration post and from a worker's hand at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…(2001). On the other hand, the carcass ratio contaminated by E. coli O157:H7 was similar to the value found by Guyon et al. (2001) and much lower than the value determined by Gun et al.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…(2001). On the other hand, the carcass ratio contaminated by E. coli O157:H7 was similar to the value found by Guyon et al. (2001) and much lower than the value determined by Gun et al.…”
Section: Resultssupporting
confidence: 83%
“…Therefore, many studies that have been performed to determine the prevalence of E. coli O157/O157:H7 on beef carcasses have reported high and low isolation rates. Guyon et al. (2001) reported a 0.4% ratio, and Gun et al.…”
Section: Resultsmentioning
confidence: 98%
“…Although this strain did not contain either of the stx loci, the fact that it contained the eaeA locus is relevant, since this locus is linked to virulence in E. coli 0157 and non-0157 Shiga toxin-producing E. coli strains (23). The present results coincide with previous reports of absence of the stx virulence genes in E. coli 0157:H7 and E. coli 0157 strains from raw meat (5,8,20,21,38). This is the first report of isolation of a large number of .rtx-negative E. coli 0157 and E. coli 0157:H7 strains from ground beef in Mexico.…”
Section: Resultssupporting
confidence: 94%
“…Studies conducted in beef abattoirs in Europe have revealed that the points of pathogen contamination include the processing equipment (8,12,16,20,25,29), plant operation personnel (8,16,20), and the plant's environment (16,20,25). These ndings, as well as those of the present study, suggest that bacterial contaminants can occur on mechanical equipment and PCS and that human factors can contribute to contamination of beef carcasses.…”
Section: Resultsmentioning
confidence: 99%